Analisa Penerapan Restorative Justice pada Perkara Pencurian oleh Anak yang Berhadapan dengan Hukum - Adi Herlambang; Diah Aju Wisnuwardhani (Postgraduate University of Merdeka Malang, 2023)
Restorative justice is implemented in Law Number 11 of 2012 concerning the juvenile justice system which upholds the dignity of the child. The application of restorative justice to criminal acts by minors is a very interesting theory to study and research because in addition to discussing justice, restorative justice is also a balanced justice system because it can provide protection and appreciation as well as the interests of the victim and the perpetrator in conflict. . The formulation of the problem in this study 1. How is the application of Restorative Justice in the crime of theft by children who are in conflict with the law in the jurisdiction of the Banggai Luwuk Police, Central Sulawesi? 2. What are the obstacles in implementing Restorative Justice in the crime of theft by children who are in conflict with the law in the jurisdiction of the Banggai Police? The research method used is empirical legal research. Children who commit criminal acts of theft are in accordance with the provisions of law number 11 of 2012 concerning the juvenile justice system regarding the implementation of diversion. In the application of restorative justice / diversion efforts are always carried out for every child who becomes a perpetrator of a crime., secondly, the obstacles experienced by the police in implementing the principles of restorative justice at the Banggai Police include: the legal factor itself, law enforcement factors, namely parties those who form or apply the law, the factor of facilities or facilities that support law enforcement, the community factor, namely the environment in which the law applies or is stipulated.